To buy or not to buy: factors that influence consumers’ intention to purchase grocery online / Sook Fern Yeo ... [et al.] - Sook, Fern Yeo; Cheng, Ling Tan; Kah, Boon Lim; Jia, Hui Wan (Universiti Teknologi MARA, Shah Alam: Accounting Research Institute (ARI), 2020)
The purpose of this study was to determine the factors influencing consumers’ online purchase intention towards online groceries. This study will contribute to people such as online sellers, government agencies and consumers themselves. Consumers are most worried about the perishability of the goods they purchase online. This is a barrier for consumers when making decisions about buying grocery online. The purposive sampling technique was most suitable for this study because online grocery shoppers are in a better position to provide the information required for this study. The questionnaires were distributed to 248 respondents in Melaka and Johor Bahru, Malaysia and only 200 were usable for analysis. The outcome of the research indicated that perceived risk, attitude, subjective norm, and perceived ease of use were factors influencing consumers’ online purchase intention of online groceries. Therefore, online grocery sellers need to take all these factors seriously to participate in a competitive industry.